Blunted Evoked Prouroguanylin Endocrine Secretion in Chronic Constipation. Issue 7 (July 2019) - Waldman, Scott A.; Tenenbaum, Renata; Foehl, Henry C.; Winkle, Peter; Griffin, Patrick
Abstract : OBJECTIVES: Prouroguanylin (ProUGN) in the intestine is cleaved to form uroguanylin (UGN), which stimulates guanylate cyclase C (GUCY2C), inducing cyclic guanosine monophosphate signaling. Paracrine release regulates fluid secretion, contributing to bowel function, whereas endocrine secretion evoked by eating forms a gut-brain axis, controlling appetite. Whereas hormone insufficiency contributes to hyperphagia in obesity, its contribution to the pathophysiology of constipation syndromes remains unexplored. Here, we compared circulating ProUGN and UGN in healthy subjects and in patients with chronic idiopathic constipation (CIC) and patients with irritable bowel syndrome with constipation (IBS-C). METHODS: Circulating ProUGN and UGN levels were measured in 60 healthy subjects, 53 patients with CIC, and 54 patients with IBS-C. After an overnight fast, the participants ingested a standardized meal; blood samples were drawn at fasting and at 30, 60, and 90 minutes thereafter, and hormone levels were quantified by enzyme-linked immunosorbent assay. RESULTS: Fasting ProUGN levels were >30% lower in patients with CIC and those with IBS-C compared with healthy subjects regardless of age, sex, or disease state. After eating, ProUGN levels increased compared with fasting levels, although the rate of change was slower and maximum levels were lower in patients with CIC and those with IBS-C. Similarly, fasting UGN levels were lower in patients with CIC and those with IBS-C compared with healthy subjects. However, unlike ProUGN levels, UGN levels did not increase after eating. DISCUSSION: These observations support a novel pathophysiologic model in which CIC and IBS-C reflect a contribution of ProUGN insufficiency dysregulating intestinal fluid and electrolyte secretion. TRANSLATIONAL IMPACT: This study suggests that CIC and IBS-C can be treated by oral GUCY2C hormone replacement. Indeed, these observations provide a mechanistic framework for the clinical utility of oral GUCY2C ligands like plecanatide (Trulance) and linaclotide (Linzess) to treat CIC and IBS-C.